Consecutive chorioangiomas in the same pregnancy: A clinical case and review of literature. Issue 3 (5th April 2022) - Germano, Chiara; Pilloni, Eleonora; Rolfo, Alessandro; Botta, Giovanni; Parpinel, Giulia; Cortese, Paolo; Cotrino, Ilenia; Attini, Rossella; Revelli, Alberto; Masturzo, Bianca
Abstract: Background and Aims: Aetiopathogenesis of chorioangioma is already unknown. Among the risk factors, hypoxia, environmental and genetic factors are believed to induce the overexpression of angiogenic cytokines promoting vascular proliferation. We reported a case of prenatally diagnosed 67 mm‐wide placental chorioangioma, which occurred at 32 weeks of gestational age, infarcted, and followed by the onset of a second infarcted chorioangioma at 35 weeks of gestational age. Besides, we discussed the hypothesis of chorioangioma aetiopathogenesis and behavior through a literature summary. Methods: We carried out a literature search of chorioangioma cases without a time interval. Therefore, we carried out a literature summary on chorioangioma risk factors and etiology, by selecting articles within a time interval from 1995 to 2021. Results: This is the first case of two consecutive chorioangiomas in the same pregnancy published in the literature. We found a possible genetic predisposition in women developing chorioangioma while infarction may be related to the abnormal structure of tumor vessels. The onset of a second lesion could reflect hypoxic stimuli following infarction and involves hypoxia‐induced factor‐1alpha, vascular endothelial growth factor, transforming growth factor‐beta, and soluble Fms‐like tyrosine kinase‐1 pathways. Chorangiosis can be coexistent and may reflect a mutual etiology in susceptible individuals. Conclusion: In a predisposed placenta, that previously generated a chorioangioma, infarction of the chorioangioma should not represent a sign for pregnancy termination, but a marker for closer monitoring to early detect the possible onset of a second chorioangioma and a higher risk of umbilical cord thrombosis.